Level of understanding about business zakat among students of IC1105C in UiTM Puncak Alam / Siti Nabila Abdul Halim - Abdul Halim, Siti Nabila (2020)
The public's response to the State Islamic Religious Council on the issue of business zakat collection has not been satisfactory for a long time. Every year, the performance of the State Islamic Religious Council as an authority on matters of zakat collection and distribution continues to be valued by the community. So, this study aims to identify the level of students’ understanding about business zakat so that Islamic community can live a good life because of the systematic zakat cycle flow. This study involving 34 students from IC1105C class. This study is done for students as they have already learned about this topic of business zakat. So, this study was done to test their level of knowledge in business zakat. This research aims to identify students’ knowledge about business zakat and measure the level understanding of Muamalat students regarding business zakat payment also evaluate students' general knowledge of zakat that being paid to Zakat Collection Center (PPZ-MAIWP). The results of the study shows that the students understand and have basic knowledge about business zakat, they also have knowledge regarding business zakat payment and they also aware about business zakat that happen nowadays and not only that, they also aware on the zakat that being paid to zakat institution. However, there are still respondents that did not have high awareness as much as the others.